'Contesting Teutomania': Robert Gordon Latham, 'race', ethnology and historical migrations. Issue 8 (17th November 2021) - Steinberg, Oded Y.
ABSTRACT: The essay elucidates the intellectual and historiographical phenomenon of migration to the forefront by engaging with the perceptions of the Teutonic/Germanic migrations of the fifth century among a few major Victorian ethnologists and historians. It focuses particularly on the unique view of the ethnologist and philologist Robert Gordon Latham (1812–88). While many Victorian historians of the mid-nineteenth century became obsessed with the Teutonic narrative, arguing that these ancient tribes had conquered vast territories of Europe, Latham, in contrast, downplayed the impact of Teutonism, discounted the vastness of the Teutonic expansion in Europe and expressed his doubts regarding the alleged Teutonic purity of the English nation. Instead, Latham advocated for an ethnological investigation, drawing conclusions which were critical of the very influential Teutonic narrative that he considered misleading, since it was founded solely on superfluous ancient historical sources. Latham's challenge of the prevailing thesis, hence, reflected a heightened mid-nineteenth century debate between ethnology and history. Rather than delving into the historical migrations themselves, the study of the perception of Teutonic migrations contributes to the understanding of how these historians and ethnologists differentiated between 'ideal' and 'destructive' historical migrations while inserting different meanings to the concepts of 'race' and 'language'.